ISSUES OF MODELING IMPROVEMENT OF THE SECONDARY EDUCATION SYSTEM (Global Economic Review: Journal of Economics, Policy, and Business Development, 2026)
The essence and potential of modeling are analyzed and characterized. Key issues in modeling for improving the secondary education system corresponding to the variable model are outlined.